2023
DOI: 10.1111/inm.13120
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐informed care in acute mental health units through the lifeworld of mental health nurses: A phenomenological study

Abstract: Trauma-informed care has gained increasing popularity in mental health services over the past two decades. Mental health nurses remain one of the largest occupations employed in acute mental health settings and arguably have a critical role in supporting trauma-informed care in this environment. Despite this, there remains a limited understanding on how trauma-informed care is applied to the context of mental health nursing in the hospital environment. The aim of this study was to explore what it means for men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…We would like to acknowledge that the methods employed in this study are built upon Wilson et al. (2023), where we initially outlined the research methodology.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We would like to acknowledge that the methods employed in this study are built upon Wilson et al. (2023), where we initially outlined the research methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Existing research on TIC in mental health settings has consistently reported that MHNs also experience trauma and re-traumatisation; with limited investigation into the role of the TIC model vis-à-vis these identified challenges (Isobel et al, 2020;Jacobwitz et al, 2015;Wilson et al, 2021). Notably, only a limited number of studies have exclusively centred on the implications of TIC for the MHN profession within hospital or acute mental health settings (Wilson et al, 2021(Wilson et al, , 2023. It is imperative to explore the implications of TIC on the MHN profession within this context to enhance the quality of care for people living with mental health conditions.…”
Section: Bac Kgrou N Dmentioning
confidence: 99%
See 2 more Smart Citations